The effects of Constraint Induced Movement Therapy on functions of cerebral palsy children: a systematic review of studies in Iran. - jamali, alireza; Amini, Malek (Iranian Journal of Child Neurology, 2018)
Objective Constraint Induced Movement Therapy (CIMT) is an intervention method that can enhance cerebral palsy children’s hand function. Cerebral palsy (CP) is a pervasive and common disorder which affects many aspects of a child life. Hemiplegic cerebral palsy affects one side of a child’s hand and has great effect on child’s independence. The aim of this study is to investigate the CIMT’s studies which have conducted in Iran. And indicate that Does CIMT’s effectiveness related to its duration and child’s age? Does CIMT have any effect of muscle tone and protective extension? Material & Methods This study is a systematic review study. For doing this study the Electronic databases such as Medlin PubMed, CINAHL… Iranian and foreigner famous journals in the fields of pediatrics such as Iranian Journal of Pediatrics (IJP), Iranian Rehabilitation Journal (IRJ)… and Google scholar and some specific key words such as CP, CIMT, and occupational therapy had been used. Results Based on the research and key words the 43 articles were found that, from those 43 articles because of lack of relevancy and other issues the 28 articles had been removed. And from obtained 25 articles, 10 of them omitted based on duplication and study’s exclusion criteria, so finally 15 articles included to this study. In Conclusion This study showed that CIMT is effective compared to no intervention but there are some inconsistencies regarding some parts of CIMT effectiveness such as CIMT effectiveness on muscle tone and protective extension.